Transcranial photobiomodulation for reducing symptoms of autism spectrum disorder and modulating brain electrophysiology in children aged 2–7: an open label study - Yuli Fradkin; Joaquin A. Anguera; Alexander J. Simon; Luis De Taboada; Eugenia Steingold (Frontiers in Child and Adolescent Psychiatry)
BackgroundSmall pilot studies have indicated that transcranial photobiomodulation (tPBM) may help alleviate symptoms of neurological conditions like depression, traumatic brain injury and Autism Spectrum Disorder (ASD).ObjectiveTo examine the effect of tPBM on the behavioral symptoms of ASD and brain electrophysiology in children aged 2–7.MethodsWe conducted an open label, one-arm study with 23 participants, aged 2–7, previously diagnosed with ASD. We delivered non-invasively to all participants pulses of near-infrared light (wavelength 850 nm, pulse 40 Hz) to cortical nodes of Default Mode Network, Broca and Wernicke areas, and occipital lobe of the brain, twice weekly for 10 weeks. The tPBM was delivered using an investigational medical device designed for this purpose. Changes in ASD symptoms were measured using pre- and post-intervention scores on the Childhood Autism Rating Scale (CARS-2, 2nd Edition). We collected electroencephalogram (EEG) data after each treatment session from all children who tolerated wearing the EEG cap to monitor changes in brain activity.ResultsThe intervention resulted in a significant 7-point reduction in average CARS-2 scores (t = 10.23, p < .0001), along with decreased delta power and increased gamma and beta power in EEG readings. The increase in gamma power was statistically significant [t(14) = 2.30, p = 0.047]. Changes in EEG power were significantly correlated with the number of sessions (delta: r(192) = −0.18, p = .013; gamma: r(192) = .19, p = .007; beta: r(192) = .15, p = .04). Improvements in CARS-2 scores were negatively correlated with changes in delta and beta power (delta: r(15) = −.59, p = .020; beta: r(15) = −.54, p = .037). No moderate or severe side effects were reported.ConclusionThis study supports the potential of tPBM as a safe and effective treatment for ASD, and it suggests that EEG measurements may serve as a useful biomarker for future research. Trial Registrationhttps://clinicaltrials.gov/ct2/show/NCT04660552